Predictors of weight stigma experienced by middle-older aged, general-practice patients with obesity in disadvantaged areas of Australia: a cross-sectional study - Spooner, Catherine (BMC Public Health, 2018)
BACKGROUND: Rates of obesity have increased globally and weight stigma is commonly experienced by people with obesity. Feeling stigmatised because of one’s weight can be a barrier to healthy eating, physical activity and to seeking help for weight management. The aim of this study was to identify predictors of perceived weight among middle-older aged patients with obesity attending general practices in socioeconomically disadvantaged urban areas of Australia. METHODS: As part of a randomised clinical trial in Australia, telephone interviews were conducted with 120 patients from 17 general practices in socioeconomically disadvantaged of Sydney and Adelaide. Patients were aged 40–70 years with a BMI ≥ 30 kg/m(2). The interviews included questions relating to socio-demographic variables (e.g. gender, language spoken at home), experiences of weight-related discrimination, and the Health Literacy Questionnaire (HLQ). Multi-level logistic regression data analysis was undertaken to examine predictors of recent experiences of weight-related discrimination (“weight stigma”). RESULTS: The multi-level model showed that weight stigma was positively associated with obesity category 2 (BMI = 35 to < 40; OR 4.47 (95% CI 1.03 to 19.40)) and obesity category 3 (BMI = ≥ 40; OR 27.06 (95% CI 4.85 to 150.95)), not being employed (OR 7.70 (95% CI 2.17 to 27.25)), non-English speaking backgrounds (OR 5.74 (95% CI 1.35 to 24.45)) and negatively associated with the HLQ domain: ability to actively engage with healthcare providers (OR 0.12 (95% CI 0.05 to 0.28)). There was no association between weight stigma and gender, age, education or the other HLQ domains examined. CONCLUSIONS: Weight stigma disproportionately affected the patients with obesity most in need of support to manage their weight: those with more severe obesity, from non-English speaking backgrounds and who were not in employment. Additionally, those who had experienced weight stigma were less able to actively engage with healthcare providers further compounding their disadvantage. This suggests the need for a more proactive approach to identify weight stigma by healthcare providers. Addressing weight stigma at the individual, system and population levels is recommended. TRIAL REGISTRATION: The trial was registered with the Australian Clinical Trials Registry ACTRN126400102162.